Secukinumab shows significant efficacy in palmoplantar psoriasis: Results from GESTURE, a randomized controlled trial - Gottlieb, Alice; Sullivan, John; van Doorn, Martijn; Kubanov, Alexey; You, Ruquan; Parneix, Anne; Hugot, Sophie; Milutinovic, Marina (Journal of the American Academy of Dermatology, 2017)
Plaque psoriasis affecting palms and soles is disabling and often resistant to treatment. Evaluate the efficacy and safety of secukinumab, an anti-interleukin 17A antibody, in subjects with palmoplantar psoriasis. In this double-blinded, randomized controlled trial, 205 subjects were randomized 1:1:1 to secukinumab 300 mg, 150 mg, or placebo. The primary endpoint was Palmoplantar Investigator's Global Assessment (ppIGA) 0 (clear) or 1 (almost clear/minimal) response at week 16. At week 16, the percentage of subjects who achieved clear or almost clear palms and soles (or ppIGA 0/1) with secukinumab 300 mg (33.3%) and 150 mg (22.1%) was superior to the percentage achieved with placebo (1.5%, P < .001). Palmoplantar Psoriasis Area and Severity Index (ppPASI) was significantly reduced with secukinumab 300 mg (−54.5%) and 150 mg (−35.3%) compared with placebo (−4.0%, P < .001). Dermatology Life Quality Index (DLQI) 0/1 responses from subjects in the secukinumab groups were also significantly higher compared with placebo at week 16 (P < .01) and pain and function of palms and soles was markedly improved with secukinumab as measured by the palmoplantar Quality-of-Life Instrument. Secukinumab 300 mg consistently showed the best outcomes. The safety profile was favorable and similar to previous studies. Lack of active comparator. In GESTURE, the largest randomized controlled trial in palmoplantar psoriasis, secukinumab demonstrated the greatest efficacy to date for treating difficult-to-treat psoriasis.